Hierarchical porous organic-inorganic composite structured catalyst, preparation method thereof and application of hierarchical porous organic-inorganic composite structured catalyst in CO2 high-value conversion

By growing porous organic materials in situ on metal foam and supporting active metals, a graded porous organic and inorganic composite structured catalyst is formed, which solves the problem of difficult catalyst recovery and huge reactor volume in CO2 hydroformylation reaction, and achieves efficient catalytic and reaction efficiency.

CN119565599APending Publication Date: 2025-03-07XIANGTAN UNIV
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510124311.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-26
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing CO2 hydroformylation reaction has problems such as difficult catalyst recovery and huge reactor volume, which affects the efficiency and feasibility of industrial applications.

Method used

Using a graded porous organic inorganic composite structured catalyst, the monolithic catalyst is formed by growing porous organic materials in situ on metal foam and supporting active metal components on its surface, and applied in fixed bed reactors.

Benefits of technology

It effectively solves the problem of difficult catalyst separation and huge reactor volume, improves the utilization rate and reaction efficiency of the catalyst, and reduces mechanical loss and reactor volume.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565599A_ABST
    Figure CN119565599A_ABST
Patent Text Reader

Abstract

The invention discloses a hierarchical porous organic-inorganic composite structured catalyst, a preparation method thereof and application of the hierarchical porous organic-inorganic composite structured catalyst in CO2 high-value conversion. The catalyst is a composite catalyst formed by taking metal foam as a catalyst carrier, loading a porous organic material on the metal foam and loading an active metal component on the porous organic material, or the porous organic material adsorbs active metal components and then is integrally embedded in the metal foam in a particle form to form the composite catalyst. The preparation method is simple, and the prepared catalyst is an integral catalyst, is easy to separate and recover, and is beneficial to industrial application. The catalyst is applied to CO2 hydroformylation reaction, and the effect is especially remarkable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a hierarchical porous organic-inorganic composite structured catalyst, a preparation method thereof, and an application thereof in high-value conversion of CO2. Background Art

[0002] At present, the effective methods for controlling CO2 emissions mainly include Carbon Capture and Storage (CCS) and Carbon Capture and Utilization (CCU). Compared with CCS technology, CCU technology shows a broader application prospect. The core of CCU technology is to capture CO2 in the atmosphere and convert it into chemical products with high economic value. A variety of chemicals such as alcohols, aldehydes, amides and hydrocarbons can be prepared through CO2 hydroformylation reaction.

[0003] CO2 hydrogenation to produce alcohols (such as methanol): CO2+3H2=CH3OH+H2O CO2 hydrogenation to produce aldehydes (such as acetaldehyde): 2CO2+5H2=CH3CHO+3H2O Preparation of amides (such as DMF) by hydrogenation of CO2: CH3NHCH3+CO2+H2=CH3CONHCH3+H2O CO2 hydrogenation to produce hydrocarbons (such as methane): CO2+4H2=CH4+2H2O CO2 hydrogenation to produce olefins (such as ethylene): 2CO2+6H2=C2H4+4H2O CO2 hydrogenation to produce aromatics (such as benzene): 6CO2+15H2=C6H6+12H2O However, due to the high stability of CO2 molecules, the conversion of CO2 usually needs to be carried out at a higher temperature to destroy its stable C=O bond. However, high temperature conditions will lead to more side reactions, reduced selectivity and increased energy consumption. Therefore, it is particularly important to develop advanced catalysts to reduce the reaction temperature and improve selectivity.

[0004] Taking the preparation of N,N-dimethylformamide (DMF) as an example, the industry currently uses methanol as a solvent and sodium methoxide as a homogeneous catalyst. The raw material carbon monoxide is introduced into the reaction system by injection, and the reaction is carried out at a certain temperature and pressure to obtain DMF with high purity. However, in the actual production process, since the reaction releases a large amount of heat, the reactor needs to be cleaned frequently to avoid blockage by crystals, which in turn produces a large amount of wastewater that is harmful to the environment. In order to develop a greener DMF preparation route, the development of technology for preparing DMF with CO2 and H2 instead of CO has long been widely concerned by academia and industry.

[0005] At present, one of the most representative research results is the preparation of DMF under mild conditions using noble metal pincer complexes as catalysts and CO2 as a carbon source developed by Professor Ding Kuiling's research group. The conversion rate of this method is close to 60%, and the product selectivity is greater than 99%. However, the catalyst used in this technology is still a homogeneous catalyst. Although it has high activity and selectivity, the separation of homogeneous catalysts and products is limited in large-scale industrial applications. In order to better meet the needs of industrial production, the development of heterogeneous catalysts has become the focus of current research on CO2 hydrogenation reactions.

[0006] As an attempt to heterogeneously transform homogeneous catalysts, researchers have developed a series of new organic carbon-based catalysts using porous polymer materials (such as metal organic frameworks (MOFs), covalent organic frameworks (COFs), porous organic polymers (POPs), etc.) as carriers. For example, covalent organic frameworks (COF-NHC-CO2) modified by N-heterocyclic carbene, Zr-based metal organic frameworks (such as MOF-808, UIO-66) and porous organic polymers loaded with Pd (Pd@POPs) can all catalyze the reaction of CO2 and amines to prepare DMF under mild conditions. These catalysts are usually reacted in a batch reactor in powder form during the synthesis process. However, there are many problems with this process, such as bulky reactors, easy loss of catalysts, and difficulty in recovering catalysts after the reaction. Therefore, it is urgent to design a porous material support strategy, that is, to organically combine porous material-based catalysts with carriers (substrates) to form a whole, and apply them to fixed bed reactors, so as to effectively solve the problems of difficult catalyst separation and bulky reactors.

[0007] Metal foam has a huge specific surface area due to its highly porous structure, which is conducive to increasing the number of active sites of the catalyst, thereby improving the catalytic efficiency. In addition, the porous structure of metal foam facilitates the diffusion of reactants and products in the catalyst bed, effectively reducing internal diffusion restrictions and further improving the reaction efficiency. At the same time, metal foam also has a stable structure, which can maintain the integrity of shape and structure during long-term catalytic reactions and has a long service life. With these advantages, metal foam has been widely studied and applied in various catalytic systems. At present, the commonly used methods for preparing metal foam-based catalysts include water-washing coating and electrodeposition. In recent years, research on the growth of active components on metal-based surfaces by hydrothermal methods has also gradually begun. For example, after growing metal organic frameworks (MOFs) on the surface of nickel foam, they can be directly used for electrocatalysis; growing MOF materials with Co and Mn as metal nodes on the surface of metal foam can be used for catalytic oxidation of volatile organic compounds (VOCs). If this monolithic catalyst is applied to high-value CO2 conversion reactions such as CO2 hydroformylation, it is expected to effectively solve the problems of difficult catalyst recovery and bulky reactors in CO2 hydroformylation reactions.

[0008] In the process of achieving high value-added conversion of CO2 to DMF using catalysts based on organic porous supports (MOF, MOP, COP, POP) in fixed-bed reactors, some key issues in catalyst design and operation still need to be addressed: (1) The catalyst should be highly active toward amines and CO2. For example, metals such as Rh, Pt, Mo, Ni, Cu, Zn, Co, and Fe can be used as active components.

[0009] (2) The porous carrier needs to be able to form an effective coordination structure with the metal. For example, carboxylic acid ligands, nitrogen-containing ligands, multidentate ligands, etc. can be used as the coordination connection between the carrier and the metal.

[0010] (3) Compared with kettle reactors, fixed bed reactors have a shorter residence time during reaction and the mass transfer process is subject to certain limitations. In order to obtain a higher carbon dioxide conversion rate, it is necessary to compensate by increasing the reaction temperature and pressure and strengthening the mass transfer method.

[0011] (4) By optimizing the operating conditions, such as selecting appropriate pressure and solvent (the solvent can also be the reactant itself), the reactants are encouraged to form a microscopic liquid phase in the hierarchical micropores of the catalyst. This helps to increase the solubility of CO2, giving reactant molecules more opportunities for collision, thereby increasing the possibility of the reaction. Summary of the invention

[0012] In view of the technical problems of difficult catalyst recovery and bulky reactor in existing CO2 high-value conversion reactions such as CO2 hydroformylation, the present invention provides a hierarchical porous organic-inorganic composite structured catalyst, a preparation method thereof, and application in CO2 high-value conversion.

[0013] The technical solution adopted by the present invention is as follows: A method for preparing a hierarchical porous organic-inorganic composite structured catalyst, using metal foam as a catalyst carrier, loading porous organic materials on the metal foam, and loading active metal components on the porous organic materials, is prepared and formed, specifically comprising the following steps: S1. Wash the metal foam and dry it; S2. dissolving the ligand of the porous organic material in a solvent to obtain a precursor solution of the porous organic material; S3. The metal foam treated in S1 is put into a precursor solution of a porous organic material, and in situ growth is performed in a high pressure reactor to obtain a solid product; S4. Wash and dry the solid product obtained in S3 and immerse it in an active metal precursor solution. Collect the solid product, dry it and reduce it with hydrogen or just dry it to obtain a hierarchical porous organic-inorganic composite structured catalyst.

[0014] The hierarchical porous organic-inorganic composite structured catalyst can also be formed by embedding the active metal component in the metal foam in the form of particles after the porous organic material absorbs the active metal component, which specifically includes the following steps: I. Wash the metal foam and dry it; II. placing porous organic material powder into an active metal precursor solution for metal adsorption; III. After the adsorption is completed, the powder is collected and dried, and the resulting powder is dispersed into a suspension, and then the metal foam obtained in step I is immersed in the suspension; IV. After the impregnation is completed, the solid product is collected, the metal foam is compressed, and the loaded catalyst powder is locked to obtain a hierarchical porous organic-inorganic composite structured catalyst.

[0015] Furthermore, porous organic materials are preferably metal organic frameworks (MOFs) with crystalline two-dimensional or three-dimensional structures, metal organic polyhedra (MOPs) with zero-dimensional structures, covalent organic frameworks (COFs) with orderly pore arrangement, covalent organic polymers (POPs) with disordered pore arrangement, and porous organic polymers (C3N4) rich in N elements; porous organic materials can anchor precious metals with catalytic activity to avoid the loss of precious metal catalysts in homogeneous catalysis. Compared with directly using metals as nodes, post-modification of anchored metals can not only accurately control the distribution and exposure of active metals and optimize catalytic active sites, but also reduce the amount of metal used and increase metal utilization and catalytic efficiency.

[0016] Furthermore, the metal foam (MF for short) is a through-hole metal foam made of at least one of copper, nickel and aluminum, or a 3D structure formed by sintering micrometers and fibers of at least one of copper, nickel and aluminum.

[0017] Furthermore, the active metal component is one of Rh, Pt, Co, Ni, Cu, Mo, Zn, and Fe.

[0018] For the loading amount of active metals, taking MOF (Cu-BDC-NH2) loaded with metal rhodium as an example, assuming that each MOF unit can coordinate with 4 Rh, then theoretically, each MOF unit can coordinate with 0.0046 mol Rh, that is, 1 g MOF can theoretically load up to 0.47 g Rh, with a mass percentage of 31wt%. If it is replaced with Fe with a lower relative molecular mass, the maximum theoretical loading amount is 20%. Due to the space limitation and cost limitation of coordination, in practical applications, the loading amount of precious metals is usually not higher than 5 wt%, and even in some loaded precious metal single atom / cluster catalysts, the loading amount of precious metals is usually between 0.01-1wt%; the loading amount of other transition metals is usually between 1-10 wt%. The present invention adopts the method of in-situ growth of MOF material on the surface of foam metal and then anchoring active metal to prepare an integral hierarchical porous organic-inorganic composite structured catalyst, and the loading amount of active metal is preferably 0.1wt%.

[0019] Furthermore, in step II, the method for preparing the porous organic material into powder is specifically as follows: placing the porous organic material and the solvent in a vacuum reactor, evacuating the reactor and reacting at 100-140° C. under its own pressure for 48-96 hours; collecting the powder, washing it, and drying it to obtain the porous organic material powder.

[0020] The hierarchical porous organic-inorganic composite structured catalyst is applied to the high-value conversion reaction of CO2, specifically: the hierarchical porous organic-inorganic composite structured catalyst is placed in a tubular fixed bed reactor for the high-value conversion reaction of CO2, the reaction pressure is not less than 1.5 MPa (the maximum reaction pressure can be controlled according to the maximum pressure of the equipment), and the reaction temperature is preferably 150°C to the decomposition temperature of DMF (under different pressure conditions, the decomposition temperature of DMF is different). By adjusting the reaction temperature and pressure, a microscopic liquid phase environment exists in the catalyst, thereby ensuring that CO2 is well dissolved in the microscopic liquid phase.

[0021] Because the catalyst is fixed on the surface of the metal foam, the problems of catalyst and product separation difficulties in kettle reactors are avoided.

[0022] In terms of operating conditions, appropriate pressure and solvent are required so that the reactants can form a microscopic liquid phase in the micropores of the catalyst, that is, different graded pores can be used as microscopic liquid containers to achieve microscopic liquid phase reactions. These graded pore structures provide more surface area, so that the reactant molecules have more opportunities to contact the reaction interface, thereby increasing the possibility of reaction; in addition, the large pores in the graded pore structure can be used as the main transmission channel, while the small pores provide more reaction sites, reducing the diffusion path of the reactant molecules inside the material and accelerating the mass transfer rate; and the graded pore structure provides more channels and reaction sites, which can reduce restrictions in the mass transfer process and improve the mass transfer capacity of the reaction.

[0023] Furthermore, CO2 high-value conversion reactions include the hydroformylation of CO2 with amines to prepare DMF, N-formylaniline, N-formylethylamide and N-cyclohexylformamide, or the hydroformylation of CO2 with olefins to prepare phenylpropanal and propionaldehyde, etc.

[0024] Furthermore, the CO2 hydroformylation reaction is preferably carried out in the presence of a solvent, and the solvents that can be used include water, alcohols, amines and other solvents with a high CO2 solubility.

[0025] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The present invention uses metal foam loaded with porous materials as a carrier to achieve hierarchical porosity from macroscopic to microscopic. These hierarchical pores of different sizes can be used as microscopic liquid containers to achieve microscopic liquid phase reactions.

[0026] (2) The present invention utilizes the modifiable functional groups in the porous material to anchor the active metal, thereby avoiding the loss of active components.

[0027] (3) Compared with powder catalysts, the catalyst of the present invention is a monolithic catalyst, which is easy to separate and recover, and is conducive to industrial application.

[0028] (4) The CO2 hydroformylation reactor in the present invention is a fixed bed reactor, which can reduce the mechanical loss of the catalyst; and the reactor volume is small, and the reactor volume for an annual production of 100,000 tons is only 2 m 3 . BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 These are scanning images of the products obtained at different stages of Example 1, wherein a is a picture of the copper foam under an optical microscope, b is a picture of the hierarchical porous organic-inorganic composite structured catalyst carrier under an optical microscope, and c is a scanning electron microscope (SEM) picture of the hierarchical porous organic-inorganic composite structured catalyst carrier.

[0030] Figure 2This is the EDS energy spectrum of the hierarchical porous organic-inorganic composite structured catalyst obtained in Example 1.

[0031] Figure 3 This is a diagram of the experimental setup used in the CO2 hydroformylation experiment, including: 1. plunger pump, 2. mass flow meter, 3. preheating chamber, 4. tubular reactor, 5. temperature controller, 6. stainless steel reaction tube, 7. sample collection tank, 8. back pressure valve, 9. gas chromatography workstation.

[0032] Figure 4 This is a graph showing the experimental results of hydroformylation of dimethylamine at 1 atmosphere pressure.

[0033] Figure 5 This is the experimental result of hydroformylation of dimethylamine at 30 atmospheres.

[0034] Figure 6 Graph showing the effect of pressure on the hydroformylation of dimethylamine.

[0035] Figure 7 This is the experimental result of ethylene hydroformylation.

[0036] Figure 8 This is the experimental result of aniline hydroformylation.

[0037] Fig. 9 This is a diagram showing the performance of the carrier and catalyst for the hydroformylation of dimethylamine.

[0038] Fig.10 This is a diagram showing the influence of different active metals on the hydroformylation of dimethylamine. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments, but the present invention is not limited thereto. Example 1

[0040] The preparation method of the hierarchical porous organic-inorganic composite structured catalyst MF-MOF-M comprises the following steps: (1) Clean the foam copper with hydrochloric acid and acetone and dry it for later use; (2) dissolving the porous layer ligand in a solvent to obtain a MOF precursor solution; (3) The treated copper metal is put into the MOF precursor solution, and after ultrasonic dispersion, it is transferred into a high-pressure reactor to react at 110°C, and the solid product is recovered after the in-situ growth is completed; (4) The solid product is washed and dried to obtain a hierarchical porous organic-inorganic composite structured catalyst carrier, which is labeled as MF-MOF; (5) dissolving the active metal salt in a solvent to obtain an active metal precursor solution; (6) Immerse the MF-MOF in the active metal precursor solution for 20 minutes and collect the solid product; (7) The collected solid product was reduced with H2 at 200 °C to obtain a hierarchical porous organic-inorganic composite structured catalyst, labeled as MF-MOF-M (M represents active metal), and the loading amount of active metal M relative to the total mass of the catalyst was 0.1 wt%.

[0041] The scanning images of the products obtained at different stages of Example 1 are as follows: Figure 1 As shown, Figure 1 a is a picture of copper foam under an optical microscope. Figure 1 b is a picture of the hierarchical porous organic-inorganic composite structured catalyst carrier under an optical microscope. Figure 1 c is the SEM image of the hierarchical porous organic-inorganic composite structured catalyst carrier. Figure 1 It can be seen that the pure copper foam has smooth pores, and the pores of the copper foam become rough after the in-situ growth of MOF. Figure 1 From the SEM image of c, it can be seen that the foam substrate is covered with spherical particles similar to 3D chestnut shells. The diameter of the spherical particles is about 5 µm, the morphology is uniform, and they are evenly distributed without agglomeration. That is, the porous material particles are neatly and evenly arranged and grown on the foam copper, and the foam substrate is tightly combined with the organic layer without any shedding phenomenon.

[0042] The EDS spectrum of the hierarchical porous organic-inorganic composite structured catalyst obtained in Example 1 is as follows: Figure 2 As shown, from Figure 2 The characteristic peaks of Cu, Rh, Cl, C, N, and O can be clearly seen, proving the successful loading of RhCl. Example 2

[0043] The preparation method of the hierarchical porous organic-inorganic composite structured catalyst MF-C3N4-M comprises the following steps: (1) Clean the foam copper with hydrochloric acid and acetone and dry it for later use; (2) dissolving urea in hot water to obtain a C3N4 precursor solution; (3) placing the C3N4 precursor solution in a muffle furnace, heating it at a rate of 55°C / min, and calcining it at 550°C for 4 hours to obtain C3N4 powder; (4) C3N4 powder was prepared into a 50 mg / mL suspension, the treated copper foam was placed in the suspension, and the mixture was repeatedly impregnated. After drying, a hierarchical porous organic-inorganic composite structured catalyst carrier was obtained, which was labeled as MF-C3N4. (5) dissolving the active metal salt in a solvent to obtain an active metal precursor solution; (6) Immerse MF-C3N4 in the active metal precursor solution for 1 hour and collect the solid product; (7) The collected solid product was compressed to lock the loaded catalyst particles, and then reduced with H2 at 200 °C to obtain a hierarchical porous organic-inorganic composite structured catalyst, labeled as MF-C3N4-M (M represents active metal), and the loading amount of active metal M relative to the total mass of the catalyst was 0.1 wt%. Example 3

[0044] The preparation method of the hierarchical porous organic-inorganic composite structured catalyst MF-COF-M comprises the following steps: (1) Clean the foam copper with hydrochloric acid and acetone and dry it for later use; (2) placing the COF monomer and the solvent in a vacuum reactor, evacuating the reactor and reacting at 120 °C under its own pressure for 72 hours; collecting the powder, washing it, and drying it to obtain COF powder; (3) dissolving the active metal salt in a solvent to obtain an active metal precursor solution; (4) The COF powder is placed in an active metal precursor solution for metal adsorption. After the adsorption is completed, the powder is collected and dried. This powder is marked as COF-M. (5) COF-M was prepared into a 50 mg / mL suspension, the treated copper foam was fully immersed in the suspension, and the solid product was collected; (6) The collected solid product was compressed to lock the loaded catalyst particles, and then reduced with H2 at 200 °C to obtain a hierarchical porous organic-inorganic composite structured catalyst, labeled as MF-COF-M (M represents active metal), and the loading amount of active metal M relative to the total mass of the catalyst was 0.1 wt%. Example 4

[0045] Application of hierarchical porous organic-inorganic composite structured catalyst in the hydroformylation of dimethylamine and CO2, specifically: Using dimethylamine as the CO2 hydroformylation substrate and water as the solvent, the prepared hierarchical porous organic-inorganic composite structured catalyst was subjected to catalytic experiments. The specific structure of the experimental device used is as follows: Figure 3 As shown, during operation, the dimethylamine aqueous solution is injected through a plunger pump, and the input amount of H2 and CO2 is controlled by a mass flow meter; the temperature of the device is controlled by program heating; the system pressure is regulated by a back pressure valve; during testing, the dimethylamine aqueous solution, H2 and CO2 are first mixed in a preheating chamber, and then introduced into a reactor containing a catalyst for catalytic reaction. Gas and liquid before and after the reaction are analyzed by gas chromatography to analyze the conversion rate under different test environments.

[0046] like Figure 4As shown, when the temperature is 190℃, the pressure is 0.1 MPa, and the molar ratio of imported CO2, H2 and dimethylamine is 1:1:1, the single-pass yield is less than 0.01% when copper foam is used as a catalyst, and almost no reaction occurs; after using MF-C3N4-Rh as a catalyst, the DMF yield is increased to 0.36%, and when MF-COF-Co is used as a catalyst, the single-pass yield of DMF is 1.10%; when MF-COF-Rh is used as a catalyst, the single-pass yield of DMF is 1.36%, and the single-pass yield of DMF obtained using MF-MOP-Rh is 2.34%; and when MF-MOF-Rh is used as a catalyst, the single-pass yield of DMF is the highest, which is 2.56%, which is 256 times that of when copper foam is used alone as a catalyst.

[0047] like Figure 5 As shown, keeping the reaction conditions unchanged and raising the reaction pressure to 3 MPa, the single-pass yield is still very low when using copper foam as a catalyst, about 0.01%; after using MF-C3N4-Rh as a catalyst, the DMF yield is increased to 15.07%, and when using MF-COF-Co as a catalyst, the single-pass yield of DMF is 5.30%; when using MF-COF-Rh as a catalyst, the single-pass yield of DMF is 22.03%; and when using MF-MOF-Rh as a catalyst, the single-pass yield of DMF can be as high as 50.49%, which is 20 times that of the corresponding experiment under the above 0.1 MPa low pressure, and 5000 times higher than when using copper foam as a catalyst alone. The single-pass yield obtained using MF-MOP-Rh is 40.3%, which is 17 times the result of the above 0.1 MPa low pressure experiment.

[0048] The above results show that MF-C3N4-Rh, MF-COF-Rh, MF-MOF-Rh, and MF-MOP-Rh all have obvious formylation catalytic activity. Under pressure reaction conditions, the reaction activity of the catalyst is higher. This is due to the high reaction pressure that creates a microscopic liquid environment inside the porous organic carrier, and the increase in pressure will greatly increase the solubility of CO2 in liquid dimethylamine, thereby effectively accelerating the reaction rate and yield. Example 5

[0049] Effect of pressure on the hydroformylation of dimethylamine with CO2 using MF-MOF-Rh as catalyst Using a graded porous organic-inorganic composite structured catalyst, the pressure of the reaction system was adjusted by a back pressure valve. When the temperature was 190°C and the molar ratio of the imported CO2, H2 and dimethylamine was 1:1:1, increasing the reaction pressure could significantly increase the DMF yield. When the pressure reached 3 MPa, the DMF yield could reach 50.49%, which is 300 times that under normal pressure (such as Figure 6As shown). According to calculation, the corresponding CO2 conversion rate can reach 52.78%, the dimethylamine selectivity is 99%, and the residence time is 17 seconds. The results show that the catalyst prepared by the present invention has obvious advantages for the hydroformylation of dimethylamine and CO2, and the increase in reaction pressure has a very significant effect on the improvement of product yield. When the pressure reaches 1.5 MPa, the product yield is obvious. Every increase of 0.5 MPa can increase the yield by several times or even nearly ten times. It is obvious that if a greater pressure is provided, the DMF yield can be further increased. The main reasons are as follows: First, with the increase of pressure, the partial pressure of CO2 in the liquid increases, and the solubility also increases, resulting in a larger concentration of CO2 in the liquid. Secondly, at the same temperature, the greater the pressure, the higher the concentration of CO2, the faster the diffusion rate of CO2 molecules, and the corresponding increase in the number of effective collisions between reactant molecules, which is conducive to the reaction. Thirdly, the increase in pressure will reduce the gas volume and flow rate, thereby increasing the residence time of the reaction, which helps to improve the reaction efficiency and product yield. Finally, the synthesis reaction of DMF is a volume-reducing equilibrium reaction, and increasing pressure can inhibit the decomposition of DMF. From this embodiment, the minimum pressure of the reaction shall not be less than 1.5 MPa.

[0050] As for temperature, the higher the temperature, the more conducive it is to the breaking of the C=O bond in CO2, and when the temperature rises, the increase in the molecular motion speed leads to an increase in the number of effective collisions between molecules, which is more conducive to promoting the formation of DMF. Therefore, the reaction temperature involving the catalytic conversion reaction of CO2 is generally not less than 150 °C. However, too high a temperature will cause the target product DMF to thermally decompose, so the maximum reaction temperature should be controlled below the decomposition temperature of DMF. Example 6

[0051] Application of hierarchical porous organic-inorganic composite structured catalysts in hydroformylation of olefins with CO2 Due to the similarity between formylation and carbonylation reactions, the catalyst was used for the carbonylation reaction of olefins, using ethylene, 1-octene and styrene as CO2 hydroformylation substrates, and the prepared hierarchical porous organic-inorganic composite structured catalyst was used for catalytic experiments. The gas and liquid before and after the reaction were analyzed by gas chromatography to analyze the catalytic performance of the catalyst for CO2 hydroformylation.

[0052] At a temperature of 160 °C and a pressure of 3 MPa, the molar ratio of the inlet CO2, H2 and ethylene was 1:1:1. After the reaction, the gas was passed through a gas chromatograph for detection. In addition to the raw gas ethylene and CO2, a certain amount of propionaldehyde (such as Figure 7As shown), it shows that the prepared catalyst also has a catalytic effect in the hydroformylation of ethylene and CO2. Ethylene can form a small amount of liquid phase environment in the pores of the catalyst under the above reaction temperature and pressure, and CO2 and ethylene are both linear molecules. The solubility of CO2 in ethylene is acceptable, so propionaldehyde is produced. When the formylation substrate is 1-octene or styrene with lower CO2 solubility, under the same operating conditions, even if octene or styrene is easier to obtain a microscopic liquid phase environment, after the reaction, the gas and liquid are passed through the gas chromatography detection except for the raw gas, and no other products are detected. The experimental results show that 1-octene and styrene did not undergo formylation reaction. The two comparative experiments show that only efficient catalysts are not enough to achieve high value-added conversion of CO2, and a liquid phase environment in which CO2 can be dissolved must be created. Example 7

[0053] Application of hierarchical porous organic-inorganic composite structured catalysts in hydroformylation of amines with CO2 Aniline was used as the CO2 hydroformylation substrate and ethanol was used as the solvent to carry out catalytic experiments on the prepared hierarchical porous organic-inorganic composite structured catalyst. The gas and liquid before and after the reaction were analyzed by gas chromatography to analyze the conversion rate under different test environments.

[0054] At a temperature of 190 °C and a pressure of 3 MPa, the molar ratio of the inlet CO2, H2 and aniline was 1:1:1. After the reaction, the liquid was passed through a gas chromatograph to detect, in addition to the raw material aniline, a certain amount of N-formylanilide (such as Figure 8 As shown), it shows that the prepared catalyst also has a catalytic effect in the hydroformylation of aniline and CO2. Comparative Example 6 of the styrene experiment shows that the microscopic liquid phase that can dissolve CO2 is crucial for the reaction.

[0055] Under the same reaction conditions, by replacing aniline with other amines, such as cyclohexylamine and ethylamine, the corresponding formylation products N-cyclohexylformamide and N-formylethylamide can be obtained, indicating that the prepared catalyst is universal in the hydroformylation reaction of amines and CO2. Example 8

[0056] The preparation method of the hierarchical porous organic-inorganic composite structured catalyst MF-MOP-M comprises the following steps: (1) Clean the metal foam with hydrochloric acid and acetone and dry it for later use; (2) dissolving the metal ligand in methanol and the organic ligand in ethanol to obtain a MOP precursor solution; (3) After the two precursor solutions are mixed, the treated metal foam is added to the mixed solution, N, N-dimethylacetamide and 2,6-lutidine are added, the solution is sealed and allowed to stand at room temperature for 12 h, and a solid product is recovered after completion; (4) The solid product is washed and dried to obtain a hierarchical porous organic-inorganic composite structured catalyst carrier, which is labeled as MF-MOP; (5) dissolving the active metal salt in a solvent to obtain an active metal precursor solution; (6) Immerse MF-MOP in the active metal precursor solution for 20 min and collect the solid product; (7) The collected solid product was reduced with H2 at 200 °C to obtain a hierarchical porous organic-inorganic composite structured catalyst, which was labeled as MF-MOP-M (M represents active metal). Example 9

[0057] The preparation method of the hierarchical porous organic-inorganic composite structured catalyst MF-COP-M comprises the following steps: (1) Clean the metal foam with hydrochloric acid and acetone and dry it for later use; (2) Organic ligand A is dissolved in dimethyl sulfoxide, and the mixture is added dropwise to a solution containing a mixed surfactant of hexadecyltrimethylammonium bromide and sodium dodecyl sulfate to form solution A; organic ligand B is dissolved in dimethyl sulfoxide, and the mixture is added dropwise to a solution containing a mixed surfactant of hexadecyltrimethylammonium bromide and sodium dodecyl sulfate to form solution B.

[0058] (3) After mixing solution A and solution B in a 250 mL single-necked flask, acetic acid was added. After the mixture was kept in a water bath at 30°C for 48 h, ammonia solution was added, followed by ethanol. The powder was collected and washed to obtain COP powder.

[0059] (4) dissolving the active metal salt in a solvent to obtain an active metal precursor solution; placing COP powder into the active metal precursor solution for metal adsorption, collecting the powder after the adsorption is completed and drying it, and the powder is marked as COP-M (M represents active metal); (5) COP-M was prepared into a 50 mg / mL suspension, the treated metal foam was fully immersed in the suspension, and the solid product was collected; (6) The collected solid product was compressed to lock the loaded catalyst particles and then reduced with H2 at 200 °C to obtain a hierarchical porous organic-inorganic composite structured catalyst, labeled as MF-COP-M (M represents active metal). Example 10

[0060] Performance of dimethylamine hydroformylation with equal volume of catalyst or support like Fig. 9As shown in the figure, when the temperature is 190℃, the pressure is 3 MPa, the molar ratio of inlet CO2, H2 and dimethylamine is 1:1:1, and the fixed bed height is fixed at 2 cm. When copper foam (0.7 g) or MOF powder (0.6 g) is used alone as a catalyst, the single-pass yields are 0.01% and 8.4%, respectively. When MOF (0.07 g) is loaded on copper foam (0.7 g) for formylation reaction, the DMF yield can reach 10.38%. Copper foam makes MOF more dispersed, promotes mass transfer of the reaction, and makes the reaction proceed at a faster rate; after Rh metal (0.006 g) is anchored on MOF powder (0.6 g), the DMF yield is increased to 16.45%. Compared with MOF powder, it shows that Rh metal has higher catalytic activity for N-containing compounds, and the catalytic performance of the catalyst is improved after anchoring MOF. After anchoring metal Rh (0.0007 g) on ​​copper foam loaded with MOF (0.07 g) for formylation reaction, the DMF yield can be further increased to 50.49%, which is five thousand times that of using copper foam alone as a catalyst and three times the conversion rate of MOF-Rh catalyst. It must be pointed out that the copper foam in the MF-MOF-Rh packed bed has no catalytic activity. The active component MOF-Rh and the loaded metal component Rh are 0.07 g and 0.0007 g, respectively, which is only 1 / 9 of the MOF-Rh packed bed. The results show that the copper foam and the MOF-Rh catalytic active component loaded on it form an unexpected synergistic effect, which greatly improves the catalytic performance of the organic-inorganic composite catalyst. Embodiment 11

[0061] Effect of Different Reactive Metals on the Hydroformylation of Dimethylamine like Fig.10 As shown in the figure, when the temperature is 190℃, the pressure is 3 MPa, the molar ratio of inlet CO2, H2 and dimethylamine is 1:1:1, and the fixed bed height is fixed at 2 cm. Using MF-MOF as a carrier, different active metals were anchored as catalysts to carry out dimethylamine hydroformylation experiments. The results show that when the active metal loading is 0.1wt%, the precious metal Rh shows the best catalytic activity.

Claims

1. A method for preparing a hierarchical porous organic-inorganic composite structured catalyst, characterized in that: The hierarchical porous organic-inorganic composite structured catalyst uses metal foam as a catalyst carrier, porous organic materials are loaded on the metal foam, and active metal components are loaded on the porous organic materials. The steps are as follows: S1. Wash the metal foam and dry it; S2. dissolving the ligand of the porous organic material in a solvent to obtain a precursor solution of the porous organic material; S3. The metal foam treated in S1 is put into a precursor solution of a porous organic material, and in situ growth is performed in a high pressure reactor to obtain a solid product; S4. Wash and dry the solid product obtained in S3 and immerse it in an active metal precursor solution. Collect the solid product, dry it and reduce it with hydrogen or just dry it to obtain a hierarchical porous organic-inorganic composite structured catalyst.

2. A method for preparing a hierarchical porous organic-inorganic composite structured catalyst, characterized in that: The hierarchical porous organic-inorganic composite structured catalyst is formed by the porous organic material absorbing the active metal component and then embedding the porous organic material in the metal foam in the form of particles, and specifically comprises the following steps: I. Wash the metal foam and dry it; II. placing porous organic material powder into an active metal precursor solution for metal adsorption; III. After the adsorption is completed, the powder is collected and dried, and the resulting powder is dispersed into a suspension, and then the metal foam obtained in step I is immersed in the suspension; IV. After the impregnation is completed, the solid product is collected, the metal foam is compressed, and the loaded catalyst powder is locked to obtain a hierarchical porous organic-inorganic composite structured catalyst.

3. The preparation method according to claim 1 or 2, characterized in that: The porous organic material is metal organic framework MOFs, metal organic polyhedron MOPs, covalent organic framework COFs, covalent organic polymer POPs or porous organic polymer C3N4 rich in N element.

4. The preparation method according to claim 1 or 2, characterized in that: The metal foam is a through-hole metal foam made of at least one of copper, nickel and aluminum, or a 3D structure formed by sintering micrometers and fibers of at least one of copper, nickel and aluminum.

5. The preparation method according to claim 1 or 2, characterized in that: The active metal component is one of Rh, Pt, Co, Ni, Cu, Mo, Zn, and Fe.

6. Use of the hierarchical porous organic-inorganic composite structured catalyst obtained by the preparation method according to any one of claims 1 to 5 in a high-value CO2 conversion reaction.

7. The use according to claim 6, characterized in that: The high-value conversion reaction of CO2 includes the hydroformylation of CO2 and amines to prepare DMF, N-formylaniline, N-formylethylamide and N-cyclohexylformamide, or the hydroformylation of CO2 and olefins to prepare phenylpropanal and propionaldehyde.

8. The use according to claim 6 or 7, characterized in that: The CO2 high-value conversion reaction is carried out in a tubular fixed-bed reactor, the reaction pressure is not less than 1.5 MPa, and the reaction temperature is 150°C to the decomposition temperature of DMF.

Citation Information

Patent Citations

  • Preparation method and application of porous composite self-supporting catalyst based on Co-MOF

    CN109647408A

  • Preparation method of metal organic framework composite material and application

    CN112675819A

  • Preparation method of foam metal in-situ growth MOFs (Metal-Organic Frameworks) hierarchical porous composite material and application in electro-adsorption of pollutants

    CN114984934A

  • Preparation method and application of bimetallic MOF anchored Pt nanocluster catalyst

    CN115770621A

  • Cerium dioxide-transition metal phosphide composite self-supporting electrode material and preparation method and application thereof

    CN116445972A